Bahasa, Adat, dan Makna : Pemanfaatan Tradisi Budaya Maumere sebagai Sumber Literasi Kritis Mahasiswa - Agustina Eupronia Sadipun; Lusia Montiana Wea; Nur Sakilla; Wahyuni Wahyuni; Yeremias Bardi (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2026)
This study is grounded in the growing concern over the weakening of students’ critical literacy skills and cultural awareness in higher education, particularly in the context of rapid digitalization and the dominance of global discourse. Local cultural traditions, especially those rooted in Maumere society, have not been optimally utilized as meaningful academic literacy resources in Indonesian language learning. This research aims to explore how Maumere cultural traditions can be integrated as sources of critical literacy to strengthen students’ interpretative, analytical, and reflective abilities. Employing a qualitative research approach, data were collected through classroom observations, in depth interviews with students and lecturers, and documentation of learning materials in Indonesian language courses at Universitas Muhammadiyah Maumere. The findings reveal that traditional texts, narratives, rituals, and oral expressions from Maumere culture contain rich linguistic, ethical, and symbolic meanings that support the development of critical reading and writing skills. The integration of cultural texts encourages students to engage more deeply with academic discourse while simultaneously reinforcing local identity and cultural sensitivity. This study implies that culturally grounded literacy practices not only enhance academic competencies but also contribute to the preservation of local wisdom within higher education learning frameworks.